2019
DOI: 10.1177/0276236619864277
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Emotion Regulation, and Creativity in Immersive and Maladaptive Daydreaming

Abstract: Daydreaming is important for creativity and the understanding of our minds and those of others. However, some adults daydream to such an extreme degree that the behavior becomes disruptive; a condition known as maladaptive daydreaming (MD). We propose that highly immersive daydreaming is not always maladaptive, and immersive characteristics of daydreaming may benefit emotional regulation, empathy, and creativity. This study consisted of 542 participants from 56 countries recruited online from MD and other comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Other components are also key elements of the disorder including the ability for vivid internal visualization, the addictive and/or compulsive aspects of the disorder, and its behavioral avoidance functions. In general, the literature suggests that maladaptive daydreaming can provide avoidance from not just the effects of severe trauma, but from general stress, conflict, loneliness, and many forms of dysphoria (1–26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other components are also key elements of the disorder including the ability for vivid internal visualization, the addictive and/or compulsive aspects of the disorder, and its behavioral avoidance functions. In general, the literature suggests that maladaptive daydreaming can provide avoidance from not just the effects of severe trauma, but from general stress, conflict, loneliness, and many forms of dysphoria (1–26).…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive daydreaming has been the subject of a series of previous studies (1–26). Somer and colleagues (12) found that maladaptive daydreaming is characterized by extensive daydreaming that occupies many hours per day, causes significant subjective distress and interferes with function, and is accompanied by extensive comorbidity (12).…”
Section: Clinical Feature Did MDmentioning
confidence: 99%
“…The Biographical Inventory of Creative Behaviors (BICB), developed by Batey (2007), has emerged as one of the more popular self-report tools to measure everyday creativity. It is cited and discussed in many major reviews of self-report tools in creativity research (Kaufman, 2019;Puryear et al, 2017;Said-Metwaly et al, 2017;Silvia et al, 2012) and has been used in research on wide-ranging topics in creativity studies (e.g., Tempest & Radel, 2019;West & Somer, 2020). To date, however, the BICB has yet to receive a detailed psychometric evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 social isolation requirements may therefore intensify MD in two possible ways. First, in line with the function of other addictions, MD may also arguably be utilized for distress regulation ( 63 , 67 ). Hence, according to the self-medication hypothesis ( 36 ), MD is likely to intensify during lockdown, especially as social isolation provides MDers with greater opportunities for the privacy needed to engage in this mental activity.…”
Section: Introductionmentioning
confidence: 99%